Effects of H2 and CO2 addition on the heat transfer characteristics of laminar premixed biogas–hydrogen Bunsen flame. (July 2016) - Wei, Z.L.; Leung, C.W.; Cheung, C.S.; Huang, Z.H.
Highlights: Biogas–hydrogen mixture was used as the fuel. The optimized hydrogen addition was determined for the BG75 fuel. The high diffusivity of hydrogen can promote the heat transfer process. The BG75 fuel is eligible to substitute methane for the heating purpose. A suitable CO2 percentage can reduce the temperature decline in the wall jet region. Abstract: The effects of H2 and CO2 on the heat transfer characteristics of the laminar premixed biogas–hydrogen flame were investigated quantitatively. The equivalence ratio was kept to 1.2 so as to obtain the stable flames, and the heat fluxes and flame temperatures of laminar biogas jet flames with different H2 (10–50%) and CO2 (25–50%) volumetric fractions were measured experimentally, and that of the methane and LPG flames were also measured for the comparison purpose. In addition, the total heat transfer rates were calculated based on the experimental data. The results show that the total heat transfer rate of impinging biogas flames can be improved evidently with the hydrogen enrichment, and the optimum hydrogen enrichment is recommended to be α H2  = 0.3 based on this study. With this hydrogen enrichment, the total heat transfer rate can be enhanced by about 20–30% at all tested heating distances. The higher flame temperature and stronger diffusivity caused by H2 addition can lead to the larger temperature gradient and more heating area with the high temperature, respectively, which are the major reasons of its promotion effects. Besides, with the same hydrogen enrichment, the BG75 flame with the less energy input has a better heating performance than the methane flame, while the BG50 flame has the minimum total heat transfer rate. CO2 exerts its influences on the heat transfer characteristics through suppressing the reaction OH + CO = CO2  + H to weaken the combustion and lowering the flame temperature by its larger specific heat capacity and the reduced proportion of the combustible component. However, the larger specific heat capacity of CO2 can also lead to the moderate reduction of flame temperature in the wall jet region, which results in the better heating performance of the BG75 flame.